2017
DOI: 10.1002/sctm.17-0138
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Cancer Cells, Cancer Stem Cells, and Mesenchymal Stem Cells: Influence in Cancer Development

Abstract: Tumors are composed of different types of cancer cells that contribute to tumor heterogeneity. Among these populations of cells, cancer stem cells (CSCs) play an important role in cancer initiation and progression. Like their stem cells counterpart, CSCs are also characterized by self‐renewal and the capacity to differentiate. A particular population of CSCs is constituted by mesenchymal stem cells (MSCs) that differentiate into cells of mesodermal characteristics. Several studies have reported the potential p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
214
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(224 citation statements)
references
References 109 publications
2
214
0
8
Order By: Relevance
“…The complex cascades of tumor invasion and metastasis, which are influenced by genetic and microenvironment changes, play an important role in the pathogenesis of malignant tumors . Aberrant EMT activation is considered a key step in the promotion of cancer metastasis, as it increases cancer cell motility and invasiveness . EMT is characterized by the loss of epithelial cell junction proteins, such as E‐cadherin, and increases in the expression of mesenchymal markers, such as N‐cadherin, fibronectin and ZEB1, and is believed to play an essential role in tumor progression and metastasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex cascades of tumor invasion and metastasis, which are influenced by genetic and microenvironment changes, play an important role in the pathogenesis of malignant tumors . Aberrant EMT activation is considered a key step in the promotion of cancer metastasis, as it increases cancer cell motility and invasiveness . EMT is characterized by the loss of epithelial cell junction proteins, such as E‐cadherin, and increases in the expression of mesenchymal markers, such as N‐cadherin, fibronectin and ZEB1, and is believed to play an essential role in tumor progression and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…40 Aberrant EMT activation is considered a key step in the promotion of cancer metastasis, as it increases cancer cell motility and invasiveness. 41,42 EMT is characterized by the loss of epithelial cell junction proteins, such as E-cadherin, and increases in the expression of mesenchymal markers, such as N-cadherin, fibronectin and ZEB1, and is believed to play an essential role in tumor progression and metastasis. 43 In our study, we found that anlotinib significantly decreased the mesenchymal markers N-cadherin, fibronectin, Slug and ZEB1.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the field has now departed from a classic view where MSC regenerate mesenchymal tissues in a cell‐for‐cell manner, secretion of growth factors and cytokines stimulating tissue regeneration probably accounting for MSC's main therapeutic benefit . MSC still exhibit the downsides of cells described exclusively in vitro following sustained proliferation: extended culture induces genetic modifications and MSC malignant transformation has been occasionally reported, adding to the inherent ability of these cells to participate in tumor stroma development . Such a genetic instability, added to unpredictable clonal selection, diversity of organ sources, and differences in culture conditions practiced in distinct laboratories, are likely to account for reported discrepancies in the biological and, by extension, therapeutic properties of these cultured cells.…”
Section: Resultsmentioning
confidence: 99%
“…63 MSC still exhibit the downsides of cells described exclusively in vitro following sustained proliferation: extended culture induces genetic modifications and MSC malignant transformation has been occasionally reported, 64,65 adding to the inherent ability of these cells to participate in tumor stroma development. 66 Such a genetic instability, added to unpredictable clonal selection, 67 diversity of organ sources, and differences in culture conditions practiced in distinct laboratories, are likely to account for reported discrepancies in the biological and, by extension, therapeutic properties of these cultured cells. Conversely, tissue-resident innate MSC forerunners should provide an unbiased picture of this class of regenerative cells.…”
Section: Resultsmentioning
confidence: 99%
“…We agree with the authors that MSCs show tropism toward pathological tissues, including cancer, and have immunomodulatory properties; thus, it could be introduced into a host without eliciting an adverse immune response [2][3][4]. Despite the tropism and immunomodulation, the major limitation in using MSCs as a drug delivery vehicle in cancer is the differential effect (inhibition/proliferation) the MSCs have on cancer cells depending on several factors, including tissue of origin of the MSCs, the individual variations in the genetic profile of the patients, and the typology of cancer [5]. Luo et al [6] used animal models to study the effect of BM-MSCs on prostate cancer.…”
mentioning
confidence: 99%